Pre-operative predictors of post-operative falls in people undergoing total hip and knee replacement surgery: a prospective study - Levinger, P.; Wee, E.; Margelis, S.; Menz, H.; Bartlett, J.; Bergman, N.; McMahon, S.; Hill, Keith (2017)
Introduction: Pain and disability often persist following hip (THR) and knee replacement (TKR) surgery predisposing patients to increased risk of falling. This study identified pre-operative predictors for post-operative falls in TKR and THR patients, and the incidence and circumstances of falls in the 12 months post-surgery. Materials and methods: A survey was undertaken of patients before THR and TKR, and was repeated 12 months post-operation. The survey included (1) medical history and medications usage, (2) pain and function, (3) health-related and physical activity and (4) fear of falls and history of falls questionnaires. Patients were classified as ‘fallers’ (≥1 fall) or ‘non-fallers’ based on prospectively documented falls in the 12 months post-surgery. Binary logistic regression was conducted to identify independent pre-operative predictors of incident falls status. Results: Eighty-two of the 243 participants (33.7%) reported ≥1 fall in the 12 months post-operatively [60 (34.1%) patients following TKR and 22 (32.8%) following THR]. The logistic regression model was statistically significant, χ2 = 24.731, p < 0.001, the model explaining 22% of the variance in falls, and correctly classifying 73.7% of cases as fallers or non-fallers. Reduced SF-36v2 general health sub-scale, increased planned physical activity and previous falls in the preceding year were predictors of falls. Those reporting ≥1 fall pre-operatively were three times more likely to fall post-operatively. Conclusion: People awaiting hip or knee joint replacement surgery might present with complex conditions that predispose them to greater risk of falling post-operation. Review of general health and history of falling is recommended pre-operatively to identify patients at risk.